Forestry Research in Uttar Pradesh - problems and Prospects - Mathur, R. S. (Indian Forester, 1991)
A brief description on recent researcb activities, problems and prospects and future programmes of forestry research is given in this paper. The past and present research techniques adopted in the State are also given in detail.